An approach for problem area elaboration and usage of organization’s strategic decisions risks - Ilina, E.P.; Slabospitskaya, O.А. (Інститут програмних систем НАН України, 2019)
A Conceptual Model is proposed for Problem Area of Strategic Decisions’ Risks within Organizational Management Systems (OS) being a result of selection, addition and interpretation operations caused by the proper Risk Object specifics and applied to the elements of regular conceptual basis for risk treatment within the other domains. The Model includes such the Concepts: Decision, Consequences for both Decision and OS; Source, Factor, Aspect and Event of Risk, Vulnerability, Hazard, Affected Property and their interrelations. Based on the Model proposed for Strategic Decision life cycle and integration of well-known Strategic Management practices the System of Strategic Decisions Risks Management Measures is considered being represented as actions with hazards, threats, vulnerabilities, risk objects and consequences. The Usage of Conceptual Model proposed is demonstrated for the Method elaboration of knowledge ambiguity- caused Risks Assessment for the decisions of Expertise using different business groups and «Value Tree» model. The Method is based on the model, where the set of knowledge ambiguity-caused Risk Factors is formalized.  The Factors’ Sources are the elements of expert problem statement. Factors‘ types are the types of non-coherent knowledge interrelations, Vulnerabilities relate to experts activity nature, Hazards are caused by the systems of expert estimates in use producing Risk Events during the process of decision life cycle. Each Risk Aspect is specialized with decision Properties being Risk targets due to Risk Events. The Method produces Risk estimates to conclude about expertise satisfactoriness and to enable selection the least risky form of its process organization.Enhancing and using of Conceptual Model proposed for Strategic Decisions Risks is advantageous for tools elaboration to support Defense Planning processes with the mechanisms of ontology based experience operation concerning with Problem Situations and Anti-crisis Measures.Problems in programming 2019; 4: 75-91